Epigenetic Therapies for Acute Myeloid Leukemia and Their Immune-Related Effects - Gambacorta, Valentina; Gnani, Daniela; Vago, Luca; Di Micco, Raffaella (Frontiers in Cell and Developmental Biology, 2019)
Over the past decades our molecular understanding of acute myeloid leukemia pathogenesis dramatically increased, thanks also to the advent of next generation sequencing (NGS) technologies. Many of these findings have however not yet translated into new prognostic markers or rationales for treatments. We know now that AML is a highly heterogeneous disease characterized by a very low mutational burden. Interestingly, the few mutations identified mainly reside in epigenetic regulators, which shape and define leukemic cell identity. In the light of these discoveries and given the increasing number of drugs targeting epigenetic regulators in development and clinical testing, great interest is emerging for the use of small molecules targeting leukemia epigenome. Together with their effects on leukemia cell-intrinsic properties, such as proliferation and survival, epigenetic drugs may as well impact on the way leukemic cells communicate with the surrounding components of the tumor and immune microenvironment. Here, we review current knowledge on alterations in AML epigenetic landscape and discuss the promises of epigenetic therapies for AML treatment. Finally, we summarize emerging molecular studies elucidating how epigenetic rewiring in cancer cells may as well exert immune-modulatory functions, boost the immune system and potentially contribute to better patient outcomes.